2005
DOI: 10.1007/s10562-005-7941-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of K, Mn and Cr on the Fischer–Tropsch Activity of Fe:Co/TiO2 Catalysts

Abstract: A range of 5% Fe/5% Co bimetallic catalysts supported on TiO 2 was promoted with 0.1%, 0.5% and 1.0% potassium, chromium and manganese respectively, and their physical properties and Fischer-Tropsch (FT) CO hydrogenation capabilities were evaluated. Low level promotion (0.1% and 0.5%) by K and Cr modestly improved the activity, decreased the selectivity to methane and increased the +C 5 fraction of the FT product while the Mn promoted catalysts retarded activity and reduced selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Duvenhage et al. also reported that Mn led to lower reducibility of bimetallic Co/Fe catalysts and decreased their catalytic activity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duvenhage et al. also reported that Mn led to lower reducibility of bimetallic Co/Fe catalysts and decreased their catalytic activity …”
Section: Introductionmentioning
confidence: 99%
“…[6] Duvenhage et al also reported that Mn led to lower reducibility of bimetallic Co/Fe catalysts and decreased their catalytic activity. [7] To solve the abovementioned problem, a full in situ characterization of the oxidation state and the local order around the active species of these materials at operational conditions is required. [8] X-ray absorption fine spectroscopy (XAFS) is mainly used to investigate the extended X-ray absorption fine structure (EXAFS) region, which reflects the local geometry of the compound, and the X-ray absorption nearedge structure (XANES) region, from which the chemical state of the metal atom can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the effectiveness of this oxide in increasing the C 5? -selectivity in the cobalt catalyzed FT reaction have been reported [11][12][13][14][15][16][17][18][19][20][21][22][23]. As an example, a study from Bezemer et al [21] showed an increase in C 5?…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid residual alkali-metals, which have been reported to be detrimental to the FT activity of Co-catalysts [21,22], a co-precipitated 30 wt% Cu/30 wt% ZnO/Al 2 O 3 catalyst was prepared according to Ref. [23].…”
Section: Catalyst Preparationmentioning
confidence: 99%